Comparison of Burr-Hole Craniostomy versus Twist-Drill Craniostomy Operations for Patients with Chronic Subdural Hematoma: A Systematic Review and Network Meta-Analysis - Mohammed Maan Al-Salihi (13105835) (2023)
Background Chronic subdural hematoma (CSDH) represents one of the most common neurologic disorders in the elderly. However, the optimum surgical option remains questionable. This study aims to compare the safety and efficacy of single burr-hole craniostomy (sBHC), double burr-hole craniostomy (dBHC), and twist-drill craniostomy (TDC) in patients with CSDH. Methods We searched PubMed, Embase, Scopus, Cochrane, and Web of Science until October 2022 for prospective trials. Primary outcomes comprised recurrence and mortality. The analysis was performed using R software, and the results were reported as risk ratio (RR) and 95% confidence interval (CI). Results Data from 11 prospective clinical trials were included in this network meta-analysis. We found that dBHC significantly decreased recurrence and reoperation rates compared with TDC (RR = 0.55, CI, 0.33–0.90 and RR = 0.48, CI, 0.24–0.94, respectively). However, sBHC showed no difference compared with dBHC and TDC. There was no significant difference among dBHC, sBHC, and TDC regarding the hospitalization duration, complication rates, mortality, and cured rates. Conclusions dBHC seems to be the best modality for CSDH compared with sBHC and TDC. It showed significantly less recurrence and reoperation rates compared with TDC. On the other hand, dBHC showed no significant difference with the other comparators regarding complication, mortality, and cure rates in addition to the hospitalization duration. Other Information Published in: World Neurosurgery License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.wneu.2023.05.022